2005
DOI: 10.3998/ark.5550190.0007.206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural investigation of some 1,4-disubstituted-2-pyrrolidinones

Abstract: A series of 1,4-disubstituted 2-pyrrolidinones was synthesized by condensation of 1-aryl-4-hydrazinecarbonyl-2-pyrrolidinones with aromatic aldehydes, acetone, 2-butanone, and 2,4-pentane-dione. Most of the reaction products have isomers owing to the amide and azomethine structural units in their molecules. Computer molecular modeling was used to study individual features of each isomer. The structures of the synthesized compounds were unambiguously elucidated by combining IR, mass, 1 H, and 13 C NMR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…N , N -Dimethyl derivatives ( II ) were reported by Elguero and Lu ,− Less frequent, but closely related to the compounds of the present study, are the N -acylhydrazones IV . …”
Section: Introductionsupporting
confidence: 69%
“…N , N -Dimethyl derivatives ( II ) were reported by Elguero and Lu ,− Less frequent, but closely related to the compounds of the present study, are the N -acylhydrazones IV . …”
Section: Introductionsupporting
confidence: 69%
“…The existence of the mixtures of stereoisomers relative to the CH=N structural fragment of the molecules was also found in the 1 H NMR spectra of the monosubstituted hydrazones 7 and 11 . Based on the studies described in the academic literature [ 73 ], as well as the data of the spectra of these compounds, we can conclude that the produced mixtures of stereoisomers with the Z- isomer predominated.…”
Section: Resultsmentioning
confidence: 80%
“…The synthesized hydrazones 7 and 11 possess amide and azomethine groups in their structures. Based on the experimental and theoretical studies presented in literature [ 73 ], it can be stated that due to the presence of the amide fragment and the restricted rotation around the CO−NH bond, the hydrazones exist in DMSO solutions as a mixture of Z/E rotamers in which the Z rotamer predominates. The clearest proof of the existence of conformers produced due to the presence of the CONH fragment was the discovery of the two sets of resonances of the NH group in the low-field region of the 1 H NMR spectra recorded in DMSO- d 6 , where a stronger-field side signal was related to the resonance of the rotamer with the Z structure.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, hydrazones 14 – 19 were synthesized, but ketones (acetone and ethyl methyl ketone, MEK) were used instead of aldehydes. The literature survey proves that hydrazones in DMSO‐ d 6 solutions due to the presence of an azomethine moiety in the molecules and a restricted rotation around the amide bond exist in the form of mixtures of E/Z isomers [26] . An analysis of the works presented in, [27–29] which are based on the comprehensive spectroscopic studies, revealed that the hydrazones of phenylamino acetic acid in DMSO‐ d 6 solutions exist in two isomeric forms, with the E/E‐ form predominating and being in dynamic equilibrium with the Z/E isomer.…”
Section: Resultsmentioning
confidence: 99%